Penerapan teknologi biopori vertikal dengan memanfaatkan larva Black Soldier Fly sebagai pengurai - Andi Dahliaty; Halida Sophia; Yuana Nurulita; Sri Helianty (Unri Conference Series: Community Engagement, 2020)
The biopore infiltration hole is a hole with a diameter of 10 cm - 30 cm with a depth of 30 cm - 100 cm which is added with organic waste and will help soil biota form a biopore hole so that it can trap the air flowing around it. Black Soldier Fly larvae are able to accelerate composting and ordering of pores in the biopore infiltration holes. Perumahan Putri Indah Kulim RT 02 RW 12 Kelurahan Mentangor rarely finds open land semisization and house widening which causes a reduction in the surface of ground air infiltration so that during the rainy season puddles easily occur and during the dry season it reduces groundwater reserves. This activity aims to provide knowledge and insight into the community about biopore infiltration holes by utilizing Black Soldier Fly larvae and inviting the public to apply this technology. This service activity begins with the socialization of the biopore infiltration holes, then introduces the tools and materials as well as direct practice in the field. The results of this activity had a positive influence on the community and many community members who wanted to apply the biopore infiltration hole technology using Black Soldier Fly larvae. This is the first step in creating a clean and healthy environment, especially in Putri Indah Kulim Housing RT 02 RW 12 Mentangor Village.